STANDAR OPERASIONAL PROSEDUR (SOP) PADA UNIT HR&GA PT BOSOWA PROPERTINDO MAKASSAR - Sampe, Valentin Laura; Fauzi, Muflih Irsyad (Politeknik STIA LAN Makassar, 2023)
Standard operating procedures (SOP) become a guideline and basis for doing a job in the most efficient and effective way by taking into account several factors such as work safety, work security and accuracy at work. This serves to improve the performance of the company PT Bosowa Propertindo Makassar because the SOP that previously existed at PT Bosowa Propertindo has not changed so that the previous SOP is no longer in accordance with the latest company rules and the use of a new system that requires SOP improvements and there are several SOPs that did not exist before, the purpose of making this thesis is to produce SOPs to optimize the performance of the Human Resource and General Affairs Unit (HR&GA). The research method used is a qualitative method by conducting interviews with parties who are in direct contact with the work to find out or determine the most effective and efficient procedures in carrying out the work which will be included in the SOP that will be made as well as conducting a document review to validate all data sources needed so that there are no fatal mistakes that can make this SOP not run optimally. The output of this thesis consists of five SOPs, namely Recruitment SOP, Payroll SOP, BPJS health registration and dismissal SOP, inventory procurement SOP and finally the SOP for submitting leave using HRIS.